Analysis and Management of Carbon Footprint in Production Warehouse Operations - Munkongtum, Chutidaj; Thriyawanich, Chalita; Ayasanond, Chitpong (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This research focuses on the analysis and management of the carbon footprint in production warehouses within the automotive and auto parts industry in Chonburi Province, Thailand, a critical area significantly impacting greenhouse gas emissions in the country. The primary objectives of this study are 1. To investigate the factors influencing carbon footprint emissions in the warehouses of the automotive and auto parts industry in Chonburi Province. 2. To analyze the greenhouse gas emissions and the amount of carbon footprint resulting from various activities in the production warehouses. 3. To propose appropriate management strategies in the warehouse activities of the automotive and auto parts industry to reduce carbon footprint emissions. The outcomes of this research are vital in supporting sustainable operations and reducing environmental impacts in the activities of production warehouses.. Methodology: This study employed a mixed-methods approach, integrating both qualitative and quantitative research methods, to examine the impact of warehouse activities on carbon footprint. The methodology included (1) Combination of Qualitative and Quantitative Research: Utilizing in-depth interviews to gather qualitative data, followed by the analysis of quantitative data from assessment forms. This approach was aimed at analyzing greenhouse gas emissions and the carbon footprint resulting from warehouse activities. (2) Selection of Population and Sample: The study included a total of 17 participants, comprising warehouse operators, academics, and experts in carbon footprint measurement, to ensure a comprehensive and expert perspective. (3) Research Tools: Development of both qualitative and quantitative research tools, with an emphasis on verifying the accuracy and validity of these tools. (4) Verification of Accuracy and Validity: Preliminary testing was conducted to assess the understandability and appropriateness of the research tools, followed by the evaluation of their reliability and validity. (5) Data Collection: Data was collected through in-depth interviews and quantitative analysis from assessment forms. (6) Data Analysis: Employed qualitative analysis and quantitative data evaluation to meet the third objective of the research. (7) Integration of Results: This involved combining data from both qualitative and quantitative approaches to present suitable management strategies in warehouse activities of the automotive and automotive parts industry to reduce carbon footprint emissions. Results: This study explores various factors affecting carbon footprint emissions in production warehouse operations, as well as analyzing and evaluating the impacts of various warehouse activities. on greenhouse gas emissions. The findings focused on identifying the activities with the most emissions. It was found that receiving and storing goods were the two main activities that had the greatest impact. Conclusion: This research proposes new approaches to managing and reducing carbon footprint in warehouses. Focusing on managing and improving operational processes, such as the use of renewable energy and the deployment of automation, reduces energy consumption and greenhouse gas emissions. The proposed approach strengthens environmental sustainability and benefits long-term production warehouse operations.